Territorial Impact Assessment, Cost Benefit Analysis and Do Not Significant Harms principle for sustainable works and plans design - Prezioso, Maria (Revista de Estudios Andaluces, 2024)
Economic, financial, and spatial analytical models are known to be integral parts of large territorial works and plans. Cost Benefit Analysis (CBA) and, newly, Territorial Impact Assessment (TIA) and Do Not Significant Harms principle (DNSH) are required to support the decision-making and evaluation process underlying climate change, initial strategic investment confirmation and final reporting. Looking at them from an economic-geographical perspective and drawing inspiration from ongoing experiences in Europe and Italy, methodological and operational guidelines are suggested in the paper to address this issue, so that both the environmental and social costs are reflected in the costs/prices/returns and in the mitigation of the public works impacts, creating a strong link between economy, territory, and environment, so that externalities can become internalities. The underlying thesis is that, knowing the territorial impacts generated by the TIA and the sustainable consistency of the project with the DNSH taxonomy, it is possible to adopt compensatory and mitigation actions, including in the related CBAs; and, at the same time, to minimise the costs resulting from the lack of policy coordination in territorial action between regional and local plans, both horizontal and vertical, when large infrastructure projects come from top-down decision as in the case of Recovery and Resilience Facility plan.